Cabin in the woods with benches and picnic tables outside - Unknown:::Creator::::::::::::
Photograph shows a cabin in the woods with benches and picnic tables in the foreground. The benches are lined up and stacked on each other and there are possible table tops leaning against a tree. The location is probably at the YWCA's Camp Ayun Map in Big Basin.